AL-Imam Ghiyath al-Din al-Dashtaki and his Approach in his Book(Al-Hashiya Ala Sharh al-Kafiya by Shihab al-Deen al-Hindi( - Ibrahim, Rawaa; Al-Tamimi, Khamis (Al-Adab Journal, 2024)
The efforts of our early scholars in serving the Arabic sciences were diverse. They left for us a valuable heritage of long and brief writings, written by ancient writers, who spent their lives collecting their materials, paying their utmost attention to their writings aiming at preserving Arabic and keeping people away of committing language mistakes or errors especially when reading and reciting Koran, the Book of Allah Almighty and the Sunnah of His Noble Prophet Muhammad, may Allah bless him and his household. There are concise compilations of summaries that are easy for students of knowledge, writings and texts to guide beginners, exquisite explanations of phrases and subtleties of structures and other grammatical compositions. It is a cell full of honey that tastes differently according to the taste and needs of persons. To serve the Holy Koran, many studies were organized, including the Arabic studies, which were advanced and developed by Arab linguists, including Al-Khalil bin Ahmed Al-Farahidi (d. 170 AH) and his student Sibawayh (d. 180 AH). Then after them came scholars who wrote over the following centuries. The seventh century AH was characterized in terms of writing by the spread of grammar books. The book Al-Kafiyya in syntax by Ibn Al-Hajib (d. 646 AH) was one of the syntactic books written in the seventh century. Scholars received that book well and were very interested in it. They wrote many explanations and clarifications on it. Moreover; they developed abbreviations and structures for it. The book Sharh Al-Kafiya by Shihab al-Din al-Dawlatabadi al-Hindi al-Zawali (d. 849 AH) was one of the commentaries written on Al-Kafiyyah, which received attention by scholars who wrote footnotes and reports on it. The most important explanation was the one written by Mir Ghiyath Al-Deen Mansur bin Muhammad bin Ibrahim Al-Dashtaki Al-Shirazi (d. 948 AH). The present paper is about a scholar who lived in the first half of the tenth century AH; however, despite the good number of his works, he did not receive an independent and clear biography that es that reveals aspects of his life and travels. We hardly know anything about him except a very little, which made him an obscure character that is unknown to many contemporary students and scholars. The present paper attempts to shed light on the author, focusing on clarifying the content of his book (Al-Hashiya ala Sharh Al-Kafiya by Al-Hindi), which is an educational book that tackles the Arabic language and syntax. It also touches upon various studies such as morphology, rhetoric, logic, argumentation, debate, speech, interpretation, and other fields. The Arabic language was not his (mother) language, but rather his language was Persian.